Evaluation of noise pollution impact on health in Dhaka city, Bangladesh - Masrur Abdul Quader; Md Mostafizur Rahman; Musabber Ali Chisty; Musabber Ali Chisty; Musabber Ali Chisty; Khawla Saeed Al Hattawi; Edris Alam; Md Kamrul Islam (Frontiers Media S.A., 2024)
ObjectivesThe purpose of this research was to look at the interrelation between adult health issues in Dhaka and noise pollution.MethodsThe methodology involved a cross-sectional survey conducted in five different land use categories, with a sample size of 1,016 individuals. A validated questionnaire that focused on sources of perceived noise pollution and health issues related to noise was used to gather subjective data for the study. Objective noise pollution was evaluated using equivalent continuous sound pressure level (LAeq).ResultsFindings revealed noise generated from road traffic are the predominant source of noise pollution, with Thursday evenings during the end of office hours being the noisiest period in Dhaka. All areas in Dhaka exceeded permissible noise levels, posing significant health risks to residents and workers. The study identifies critical gaps in existing noise regulation policies and enforcement.ConclusionOverall, this study underscores the urgent need for comprehensive noise pollution mitigation strategies, including innovative technologies, real-time monitoring systems, and public awareness campaigns. Further studies in diverse urban contexts are recommended to enhance the understanding of noise pollution's long-term impacts on vulnerable populations.